2013
DOI: 10.1007/s00572-013-0482-2
|View full text |Cite
|
Sign up to set email alerts
|

Global sampling of plant roots expands the described molecular diversity of arbuscular mycorrhizal fungi

Abstract: We aimed to enhance understanding of the molecular diversity of arbuscular mycorrhizal fungi (AMF) by building a new global dataset targeting previously unstudied geographical areas. In total, we sampled 96 plant species from 25 sites that encompassed all continents except Antarctica. AMF in plant roots were detected by sequencing the nuclear SSU rRNA gene fragment using either cloning followed by Sanger sequencing or 454-sequencing. A total of 204 AMF phylogroups (virtual taxa, VT) were recorded, increasing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
186
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(196 citation statements)
references
References 62 publications
6
186
1
3
Order By: Relevance
“…AMF have been investigated in a multitude of environments, from tropical forests to agro-environments and sand dunes (Turrini andGiovannetti, 2012 andÖpik et al, 2013). However, to the best of the authors' knowledge, AMF biodiversity has never been described in such environments as truffle-grounds in which AMF could interact directly with herbaceous plant roots and indirectly with ectomycorrhizal fungi.…”
Section: Discussionmentioning
confidence: 99%
“…AMF have been investigated in a multitude of environments, from tropical forests to agro-environments and sand dunes (Turrini andGiovannetti, 2012 andÖpik et al, 2013). However, to the best of the authors' knowledge, AMF biodiversity has never been described in such environments as truffle-grounds in which AMF could interact directly with herbaceous plant roots and indirectly with ectomycorrhizal fungi.…”
Section: Discussionmentioning
confidence: 99%
“…As AMF are obligately symbiotic organisms, both the host species (Lovelock et al 2003;Helgason et al 2007;Syḱorová et al 2007;de Oliveira Freitas et al 2014) Kivlin et al 2011;Öpik et al 2013) factors will influence AMF community structure but, in many cases, it is difficult to clearly disentangle these due to edaphic sorting of the host plant.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in root colonization ability might be a result of the physiological and functional characteristics of AMF species (Fitter 2005), and may be influenced by specific adaptations to environmental conditions prevalent at the place where the AMF species originated from (Marulanda et al 2007;Lekberg and Koide 2008). Due to such adaptations, AMF species or even different strains of a same species might be either restricted or dominant in an ecosystem, leading to distinct AMF communities in different continents and climatic zones (Opik et al 2006;Opik et al 2013). Egerton-Warburton et al (2007) and Querejeta et al (2009) reported a dominance of Glomus species in AMF communities in soils of xeric habitats.…”
Section: Discussionmentioning
confidence: 99%